Magical realism in The Midnight Library by Matt Haig: An analysis based on Wendy B. Faris’s framework - Nisrina Alimah Adriyanto; Henny Suharyati; Dyah Kristyowati (Journal Albion : Journal of English Literature, Language, and Culture, 2025)
This study analyses the elements of magical realism in The Midnight Library by Matt Haig using Wendy B. Faris’s five key characteristics of magical realism: the irreducible element, the phenomenal world, unsettling doubts, merging realms, and disruptions of time, space, and identity. The research uses a qualitative descriptive method to examine how magical experiences are portrayed through the protagonist Nora Seed as she navigates an in-between space between life and death. The findings show that Faris’s framework is applicable to this contemporary Western novel, expanding the use of magical realism theory beyond its Latin American roots. Moreover, the narrative technique of stream of consciousness is also identified as a key device that enhances the internalization of magical experiences. This research contributes to the broader discourse on magical realism in global literature and its relevance to psychological and existential themes.